Saúde bucal do idoso na perspectiva do cuidador - Oliveira, Ana Giovana Medeiros de (2018)
Elders with impaired oral health have many limitations for food, especially if they use total prosthesis whose retention and stability requirements are unsatisfactory, leading to a low nutritional supply. Within this perspective, the present research is justified by the scarcity of studies about elders’ oral health from the caregiver’s point of view, as well as the preservation of the elders’ general health and the self-care with its maintenance, and the caregiver is responsible for making their actions of extreme importance. Therefore, the following question emerges: What is the impact of the caregiver’s actions in the elder’s oral health? To answer this question, the objective of this study is to evidence, in the scientific literature, the caregiver’s actuation in the elder’s oral health care. This is an integrative review, which used the following descriptors in Portuguese: idoso AND cuidador AND saúde bucal AND gerodontologia, as well as their corresponding in English: elderly AND caregiver AND oral health AND gerodontology. The research was conducted in national and international virtual libraries and databases: Scopus, CINAHL, PubMed, Web of Science, Virtual Health Library and the Portal of Journals of the Coordination for Higher Level Personnel Improvement, in the period from July to December 2017. The inclusion criteria were: full articles available in the databases and libraries previously mentioned, published in English or Portuguese, in the period from 2012 to 2017, which were in accordance with the descriptors and the guiding question. There was exclusion of literature reviews, editorials, experience reports, letters, chapters of books and articles duplicates. The search resulted in 12 articles in their entirety. The results show that caregivers of institutionalized elders or those assisted at home lack practice and knowledge about elders’ oral hygiene and health, damaging, in this way, assistance, which may, consequently, trigger oral and/or systemic diseases, such as periodontal diseases, edentulism, aspiration pneumonia, bacterial endocarditis, among others, understanding that oral and general health are interlinked. Most caregivers report having knowledge about methods of oral hygiene, but in practice, this is not effective, because they do not have the ability to do so. Associated with this disability, there are work overload and the large number of elders under their supervision, considering both institutionalized elders as those who live at their own home. Thus, these caregivers have difficulty providing a more effective and continuous healthcare regarding attention to elders’ oral health, who also present resistance to oral hygiene, which are crucial factors for poor assistance and hygiene. The general health is linked to oral health and became the research object of many studies, considering the changes in the stomatognathic system that occur in the elderly population and affect the quality of life.